Vemurafenib Combined With Trametinib Significantly Benefits the Survival of a Patient With Stage IV Pancreatic Ductal Adenocarcinoma With BRAF V600E Mutation: A Case Report - Wang, Ziyao; He, Du; Chen, Chen; Liu, Xubao; Ke, Nengwen (Frontiers in Oncology, 2022)
Vemurafenib and Trametinib have a lot of successful experience in the treatment of unresectable or metastatic melanoma with BRAF V600E mutation. However, it has not been reported in the treatment of advanced pancreatic ductal adenocarcinoma (PDAC). We report a 66-year-old male who was diagnosed as PDAC with multiple metastases of abdominal cavity and liver according to pathological examination. After 3 cycles of Gemcitabine plus Nab-paclitaxel (GA) regimen chemotherapy, the patient's liver metastasis progressed, and the patient could not continue to receive chemotherapy because of the poor physical condition. BRAF V600E mutation was found by genetic detection in this patient, so targeted therapy with Vemurafenib combined with Trametinib was performed and the follow-up period was up to 24 months. To the best of our knowledge, this is a rare report that patients with stage IV PDAC with BRAF V600E mutation can receive significantly survival benefits from targeted therapy with Vemurafenib combined with Trametinib. This report provides experience for the use of these two drugs in patients with advanced PDAC.